1990
DOI: 10.1111/j.2042-7158.1990.tb07015.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Post-junctional α-Adrenoceptor-mediated Responses in the Rat Gastric Fundus In-vitro

Abstract: The effects of alpha 1- and alpha 2-adrenoceptor agonists on smooth muscle tone and on cholinergic excitatory and non-adrenergic, non-cholinergic inhibitory responses to field stimulation have been investigated in the rat gastric fundus in-vitro. None of the alpha-adrenoceptor agonists tested, noradrenaline, phenylephrine, cirazoline, guanoxabenz or UK-14,304 showed any contractile effects at concentrations up to 30 microM. In preparations where tone was raised by barium (0.5-2 mM), the mixed alpha 1- and alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1991
1991
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
(20 reference statements)
0
13
0
1
Order By: Relevance
“…Prejunctional modulation of NANC neurotransmission in the gastrointestinal tract was previously decribed in only a few tissues (see Introduction); in the rat gastric fundus (MacDonald et al, 1990) and the guinea-pig proximal colon (Kojima et al, 1988), the prejunctional inhibition of the NANC relaxations was reported to be mediated by (X2-adrenoceptors. Recently Lefebvre & Smits (1992) Lefebvre, 1988), complicating the study of prejunctional regulation of NO release.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prejunctional modulation of NANC neurotransmission in the gastrointestinal tract was previously decribed in only a few tissues (see Introduction); in the rat gastric fundus (MacDonald et al, 1990) and the guinea-pig proximal colon (Kojima et al, 1988), the prejunctional inhibition of the NANC relaxations was reported to be mediated by (X2-adrenoceptors. Recently Lefebvre & Smits (1992) Lefebvre, 1988), complicating the study of prejunctional regulation of NO release.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge, together with morphological evidence demonstrating the presence of NO synthase in its myenteric neurones (unpublished observations), make the ileocolonic junction an interesting model to study possible prejunctional regulation of NO release. Since the ileocolonic junction receives a prominent adrenergic innervation and since prejunctional modulation of NANC neurotransmission via adrenoceptors has been described (Kojima et al, 1988;MacDonald et al, 1990;Lefebvre & Smits, 1992), we suggest a possible prejunctional adrenergic regulation of the NO release at the canine ileocolonic junction.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, their are many other possibilities since, in the myenteric plexus of the guinea-pig gastric fundus, Mawe et al (1989) demonstrated the presence of serotonin-containing neurons, and neurons with immunoreactivity for substance P, calcitonin gene-related peptide, neuropeptide Y and tyrosine hydroxylase, as well as VIP. Smooth muscle of the rat gastric fundus can be relaxed by activation by catecholamines of (~1 -adrenoceptors and atypical P-adrenoceptors MacDonald et al 1990); however, it is unlikely that these were involved in the present study since the rats were pretreated with reserpine to deplete catecholamine stores. The nature of the mediator of the residual response to nicotine after blocking nitrergic and VIPergic mechanisms will be explored in a future study.…”
Section: )mentioning
confidence: 97%
“…A noradrenergic control of the function of these sensory neurones has been demonstrated in different peripheral preparations. Noradrenaline (NA) and neuropeptide Y, co-stored in sympathetic nerve terminals, and released together by electrical field stimulation (Lundberg et al, 1982;Fried et al, 1985), suppress the non-adrenergic non-cholinergic contractions evoked by antidromic nerve stimulation in guinea-pig bronchi and rat gastric fundus through an action on specific pre-junctional receptors (Grundstrom et al, 1984;Grundstrom & Anderson, 1985;Matran et al, 1989;MacDonald et al, 1990). The influence of NA on the efferent function of capsaicinsensitive neurones in the heart has not been investigated; therefore in the present study we have evaluated the effect of NA and other adrenergic agonists and antagonists on the response of these neurones to electrical field stimulation in guinea-pig isolated atria.…”
Section: Introductionmentioning
confidence: 99%